A study on the awareness and utilization of interactive media in learning the Bugis language and Lontara script / Muhammad Syahmi Salleh - Salleh, Muhammad Syahmi (2023)
The Bugis ethnic group possesses a distinct identity, culture, and traditions that have been preserved over time. These aspects include marriage customs, language usage, writing systems, and the transmission of traditional cuisine. The Bugis community's rich heritage has been maintained till present day. One notable aspect of Bugis culture is Lontara, an ancient writing system found in old Palm-leaf manuscripts originating from the Bugis-Makassar region. These manuscripts contain valuable knowledge on various subjects such as history, science, traditions, and laws. Over time, the writings were adapted into the Buginese language, which is widely spoken by Bugis natives in Malaysia and other parts of the world. However, most of the modern Bugis community, have unfortunately forgotten about Lontara including the Bugis language. The main reason for this is the lack of practice and usage of the language among the native Bugis themselves. This contributes to the decline of other cultural elements, such as their traditional customs. Therefore, it is crucial to protect and maintain traditional culture by conducting in-depth studies and research. This will help us gain a deeper understanding of our roots and provide alternative ideas to engage and attract people, especially the younger Bugis generation, to learn more about Bugis culture, starting with the language.